INTEGRATING ARTIFICIAL INTELLIGENCE WITH HUMAN ANATOMY: A NEW FRONTIER IN INTELLIGENT ANATOMICAL ANALYSIS AND EDUCATION - Khabibulla Pulatov; Sabina Kholboyeva; Farangiz Mirzayeva (Web of Journals Publishing, 2025)
The integration of artificial intelligence (AI) into the field of anatomy represents a transformative step toward precision understanding of the human body. Traditional anatomical education and analysis rely heavily on static visualization and manual interpretation, whereas AI enables dynamic, data-driven exploration of human structures. This study proposes a novel framework that combines deep learning, medical imaging, and computational modeling to create adaptive anatomical systems capable of real-time recognition, prediction, and simulation of biological structures. Using neural networks trained on high-resolution histological and radiological datasets, the system—termed NeuroMorphAI—can identify complex anatomical patterns, detect microstructural variations, and reconstruct three-dimensional models with unprecedented accuracy. The research highlights the potential of AI-anatomy integration in medical education, clinical diagnostics, and surgical planning, demonstrating how intelligent systems can augment human anatomical expertise rather than replace it. This pioneering approach lays the foundation for a new discipline—computational anatomy intelligence—bridging the gap between biological complexity and artificial cognition.
Keywords: Artificial Intelligence, Anatomy, Computational Modeling, Medical Imaging, Neural Networks, Education, Simulation.